Measurement of Service Quality at BSI KCP Banjar Using CARTERD - Hidayatullah, Lutfie; Pratama, Novandra Rhezza; Farizal, Farizal (Review of Accounting and Business, 2021)
The current digitalization of the banking sector continues to experience massive and innovative developments because to be able to compete with other competitors, a bank is required to have an advantage with the technology used in addition to efficiency operational. So that customers get a memorable experience. The purpose of this study is to determine the dimensions and attributes used to measure the quality of service at Bank Syariah Indonesia (BSI) Branch Office Banjar, and how the quality of service at BSI. The method used is by distributing questionnaires to 101 BSI customers as respondents using SERVQUAL method and CARTERD dimensions, (Compliance, Assurance, Reliability, Tangible, Empathy, Responsiveness and Digitalization), the data declared were valid using validity tests person-correlation product-moment, Cronbach's Alpha reliability tests value on perceived is 0.960 and expectation is 0.922, which means reliable. The 5 attributes that have the biggest gap are vehicle parking facilities, no loan interest, no savings interest, the management team has extensive knowledge, and pleasant service (fast service time). Based on the IPA graph, the attributes included in quadrant 1 should receive special attention, namely, the attributes of 3 Islamic banks should provide Islamic products and services, attributes of 4 Islamic banks should provide interest-free loan provisions, attributes of 19 service office locations. This research shows that the compliance dimension must be a major concern because it is a core competency of Islamic banks, management would be better improve compliance in line with improvement investments in digitalization development.